2013 Joint IFSA World Congress and NAFIPS Annual Meeting (IFSA/NAFIPS) 2013
DOI: 10.1109/ifsa-nafips.2013.6608605
|View full text |Cite
|
Sign up to set email alerts
|

Correlations from conjugate and dual intuitionistic fuzzy triangular norms and conorms

Abstract: This paper aims to study the correlation between intuitionistic fuzzy sets obtained as image of intuitionistic fuzzy t-norms and t-conorms. We consider the action of automorphisms and the class of strong fuzzy negations in order to verify the conditions under which the correlation coefficient related to such fuzzy connectives and their corresponding conjugate and dual constructions are obtained. We attend to present algebraic expressions of correlation relationship by considering t-representable intuitionistic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 9 publications
(15 reference statements)
0
2
0
Order By: Relevance
“…An A-IFS considers the informations of these degrees and also providing the hesitation (uncertainty) margin related to the Atanassov's intuitionistic fuzzy index (A-IFIx), as reported by approach. This approach leads to a great numbers of studies, all of them are closely connected with the correlation coefficient (A-CC) [Reiser et al 2013, Bertei et al 2016, Bertei and Reiser 2018, Bertei et al 2021] between two intuitionistic fuzzy sets, mainly those applied to processes of decision-making, such as clustering analysis [Meng et al 2016], digital image processing and medical diagnosis [Bertei and Reiser 2019].…”
Section: Introductionmentioning
confidence: 99%
“…An A-IFS considers the informations of these degrees and also providing the hesitation (uncertainty) margin related to the Atanassov's intuitionistic fuzzy index (A-IFIx), as reported by approach. This approach leads to a great numbers of studies, all of them are closely connected with the correlation coefficient (A-CC) [Reiser et al 2013, Bertei et al 2016, Bertei and Reiser 2018, Bertei et al 2021] between two intuitionistic fuzzy sets, mainly those applied to processes of decision-making, such as clustering analysis [Meng et al 2016], digital image processing and medical diagnosis [Bertei and Reiser 2019].…”
Section: Introductionmentioning
confidence: 99%
“…In our previous work [1,2], it is shown that the conjugate of an interval-valued Atanassov's intuitionistic fuzzy negation not only preserves the main properties of its corresponding fuzzy negation but also of two other ones, the intuitionistic fuzzy negation and intervalvalued fuzzy negation. Moreover, we introduce an extension of the intuitionistic fuzzy index as well as study basic concepts related to the correlation index in the sense of [3], 2 which are discussed in terms of fuzzy connectives, by considering the Atanassov's Intuitionistic Fuzzy Logic.…”
Section: Introductionmentioning
confidence: 99%